Palynological Evidence on Palaeoclimate of Jaisalmer Basin and Desertification of Thar Desert - Lukose, N G (Annals of Arid Zone, 2016)
The palaeo-climate of Jaisalmer basin, during Albian to Sub-Recent times inferred on the basis of palynological studies carried out on various rock formations representing the above geological period, is discussed On the basis of the evidences, it has been postulated that semihumid conditions started during the Late Cretaceous and Early Tertiary period gave way to progressive and continued aridity during the successive geological periods, thereby leading to the formation of the Thar desert.